A simple asymptotically optimal filter over an infinite horizon. (2001) - Chigansky, P.; Liptser, R.; Bobrovsky, B. Z.
Abstract : A filtering problem over an infinite horizon for a continuous time signal and discrete time observation in the presence of non-Gaussian white noise is considered. Conditions are presented, under which a nonlinear Kalman type filter with limiter is asymptotically optimal in the mean square sense for long time intervals given provided the sampling frequency is sufficiently high.